Chimeric RXFP1 and RXFP2 Receptors Highlight the Similar Mechanism of Activation Utilizing Their N-Terminal Low-Density Lipoprotein Class A Modules - Bruell, Shoni; Kong, Roy C.; Petrie, Emma J.; Hoare, Brad L.; Wade, John D.; Scott, Daniel J.; Gooley, Paul R.; Bathgate, Ross (Frontiers in Endocrinology, 2013)
Relaxin family peptide (RXFP) receptors 1 and 2 are unique G-protein coupled receptors in that they contain an N-terminal low density lipoprotein type A (LDLa) module which is necessary for receptor activation. The current hypothesis suggests that upon ligand binding the LDLa module interacts with the transmembrane (TM) domain of a homodimer partner receptor to induce the active receptor conformations. We recently demonstrated that three residues in the N-terminus of the RXFP1 LDLa module are potentially involved in hydrophobic interactions with the receptor to drive activation. RXFP2 shares two out of three of the residues implicated, suggesting that the two LDLa modules could be interchanged without adversely affecting activity. However, in 2007 it was shown that a chimera consisting of the RXFP1 receptor with its LDLa swapped for that of RXFP2 did not signal. We noticed this construct also contained the RXFP2 region linking the LDLa to the leucine-rich repeats. We therefore constructed chimeric RXFP1 and RXFP2 receptors with their LDLa modules swapped immediately C-terminally to the final cysteine residue of the module, retaining the native linker. In addition, we exchanged the TM domains of the chimeras to explore if matching the LDLa module with the TM domain of its native receptor altered activity. All of the chimeras were expressed at the surface of HEK293T cells with ligand binding profiles similar to the wild-type receptors. Importantly, as predicted, ligand binding was able to induce cAMP based signalling. Chimeras of RXFP1 with the LDLa of RXFP2 demonstrated reduced H2 relaxin potency with the pairing of the RXFP2 TM with the RXFP2 LDLa necessary for full ligand efficacy. In contrast the ligand mediated potencies and efficacies on the RXFP2 chimeras were similar suggesting the RXFP1 LDLa module has similar efficacy on the RXFP2 TM domain. Our studies demonstrate the LDLa modules of RXFP1 and RXFP2 modulate receptor activation via a similar mechanism.